L’intégration d’étrangers dans la santería et le culte d’Ifá à La Havane - Emma Gobin (Ateliers d'Anthropologie)
Since the 1990s, Cuban santería and Ifá (also called ‘complex of ocha-Ifá’) have been undergoing a significant expansion. A growing number of American and European foreigners visit the island for initiatory or ritual purposes. Based on a detailed ethnography stemming from a field study conducted during the 2000s (mostly in Havana), this paper offers an extensive overview of this phenomenon, focusing on its effects on the ritual and discursive practices of Cuban santeros and babalaos (santería and Ifá priests). After considering the internal logic involved in the construction of a priest’s career, it examines how the integration of foreigners influences the interactional construction of religious statuses and the development of specific relationships to oneself and to others in connection with local ‘empowerment’ rationales. Two levels of analysis are distinguished: that of the ‘common’ initiates and that of erudite and/or politicized ‘elite’ groups. Both highlight not only the rivalries at play in the Afro-Cuban religious field, but also the intense critical and reflexive attitude that santeros and babalaos maintain towards their own practice, as well as some of the innovative logic inherent to this world but intensified by this new situation. In particular, the paper argues that the bonds Cuban priests establish with foreigners—through ritual kinship or through increasingly numerous ceremonial collaborations with initiates from abroad—constitute an additional component in the micro-conflicts that ordinarily pervade religious practice and can, on a larger scale, have an influence on the power relations that create oppositions between different ‘elite’ groups (some of them deeply committed to projects of ritual ‘reform’). While adopting a predominantly micro-political interpretation, the paper also considers the ritual implications of these dynamics.